Analisis Pengaruh Beban Pajak Kini, Beban Pajak Tangguhan, Dan Basis Akrual Terhadap Manajemen Laba - Amanda, Felicia; Febrianti, Meiriska (Ultimaccounting Jurnal Ilmu Akuntansi, 2015)
The purpose of this study is to analyze the effect of current tax, deferred tax expense, and accrual basis towards earnings management. The object of this study are manufacturing companies in consumer goods sector that are listed in Bursa Efek Indonesia for period 2011-2013.Selection of the sample is determined based on purposive sampling method. The sample used in the study are 19 manufacturing companies in consumer goods sector that are listed in Bursa Efek Indonesia for period 2011-2013, presenting and publishing financial statements on BEI's official site in Indonesian Rupiah, that have been audited by an independent auditor per 31 December, contains data related to current tax expense and deferred tax expense, and have scaled earning change value in range 0 – 0,06 and -0,09 – 0. The data used in this study are secondary data, the annual financial statements audited by an independent auditor. Data analysis method used is logistic regression.The results of this study are (1) current tax expense has significant effect towards earnings management, (2) deferred tax expense does not have significant effect towards earnings management, (3) accrual basis does not have significant effect towards earnings management, (4) current tax expense, deferred tax expense, and accrual basis simultaneously have significant effect towards earnings management. Keywords: accrual basis, current tax expense, deferred tax expense, earnings management.